Komparasi Laporan Keuangan PT. BPR Anugerahdharma Yuwana Cabang Ambulu Kabupaten Jember - Fitriana, Alya; Epriliyana, Nike Norma; Lestari, Hari Budi (Program Studi Akuntansi Fakultas Ekonomi Universitas PGRI Argopuro Jember, 2024)
This study aims to explain the comparison of financial statements at PT BPR Anugerahdharma Yuwana Jember Ambulu Branch, Jember Regency in 2021 and 2022. The research method is descriptive research with a qualitative approach. The data collection techniques used are literature study, interviews, documentation, and observation. While the data used are primary and secondary data obtained from PT BPR Anugerahdharma Yuwana Ambulu Branch, Jember Regency. Company ratios are calculated based on liquidity ratios, solvency ratios, and profitability ratios. The results showed that compared to 2021, in 2022 the liquidity, solvency and profitability of PT. BPR Anugerahdharma Yuwana Jember Ambulu Branch, Jember Regency has increased.